2016
DOI: 10.1515/mms-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

On Employing a Savitzky-Golay Filtering Stage to Improve Performance of Spectrum Sensing in CR Applications Concerning VDSA Approach

Abstract: In this paper, a filtering stage based on employing a Savitzky-Golay (SG) filter is proposed to be used in the spectrum sensing phase of a Cognitive Radio (CR) communication paradigm for Vehicular Dynamic Spectrum Access (VDSA). It is used to smooth the acquired spectra, which constitute the input for a spectrum sensing algorithm. The sensing phase is necessary, since VDSA is based on an opportunistic approach to the spectral resource, and the opportunities are represented by the user-free spectrum zones, to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The proposed method replaces it with the SG filter on each ICA component [35]. In addition, Angrisani et al reported that the SG filter could increase the frequency perception of signals with low SNR more than the MA [47]. The order and window size of the SG filter are fourth and 25 units (SG_order = 4, frameLength = 25).…”
Section: E Proposed Ippg Methods On Non-facial Regionsmentioning
confidence: 99%
“…The proposed method replaces it with the SG filter on each ICA component [35]. In addition, Angrisani et al reported that the SG filter could increase the frequency perception of signals with low SNR more than the MA [47]. The order and window size of the SG filter are fourth and 25 units (SG_order = 4, frameLength = 25).…”
Section: E Proposed Ippg Methods On Non-facial Regionsmentioning
confidence: 99%
“…The window length neutralizes the high-frequency noise contribution for the second degree of freedom by smoothing its fluctuations through polynomial fitting 32,33 . The SG filter searches for the optimal n + 1 polynomial coefficients for a given n-degree polynomial to best suit the raw data and assesses the outcome in the window center 34,35 . The polynomial function was applied to the signal point by point.…”
Section: Spectral Pre-treatmentmentioning
confidence: 99%
“…This paper uses the moving window least squares polynomial smoothing algorithm (Savitzky-Golay Smoothing) for data smoothing. The Savitzky-Golay Smoothing algorithm [10][11][12] was originally proposed by Savitzky and Golay in 1964 for smoothing and noise reduction of data streams and is now widely used in the image processing field. The algorithm is a least square based local fitting method that starts at the beginning of the stream and smooths the stream within a predetermined smoothing window, sliding backwards through the smoothing window until the end of the stream, the most important feature of the algorithm is that the shape, width and tendency of the stream remain unchanged while smoothing the data.…”
Section: Grey Gm(11) Prediction Model Improvementmentioning
confidence: 99%